Parent-child TV interaction: the importance of perspective - Austin, Erica Weintraub (Journal of broadcasting & electronic media, 1992)
Research regarding the influence of parents on their children's television viewing has produced contradictory results. Factors researchers looked at included whether the television guidance was positive or negative, perceived to be unfocused or restrictive, and the age of the children. The contradictory results reveal a lack of correlation between the views of parents and children, and misunderstanding of what was measured in the research.